Negotiations for the Trans-Pacific Partnership agreement: Evaluation and implications for East Asian regionalism - Inkyo Cheong (Asian Development Bank Institute (ADBI), 2013)
The Trans-Pacific Partnership (TPP) agreement seems to have reached a crossroads: it could either be a building block toward achieving economic integration in Asia and the Pacific, or trigger the formation of two large trade blocs which will work independently of one another. When the Government of Japan announced its participation in the TPP negotiations in March 2013, the partnership began to attract greater interest from other East Asian countries. This paper analyzes the progress and major issues regarding the current TPP negotiations which are being led by the United States, and draws implications for East Asian economic integration.
Keywords: F15; F53; O53; 330; trans-pacific partnership; tpp; republic of korea; economic integration; asia pacific; east asian countries; Regionale Wirtschaftsintegration; Regionale Wirtschaftsintegration; Handelsabkommen; Asiatisch-pazifischer Raum